Avaliação das características de diferentes metacaulins e sua influência na estrutura interna do concreto e em propriedades ligadas à durabilidade - Alves, Rodrigo Teodoro (2016)
Cementitious materials have been used since antiquity. The development of silica fume as a pozzolana has afforded significant improvements to concrete technology. Now, new high performance mineral admixtures have come to light, such as highly-reactive metakaolin. This material has presented great results, trough more than a decade, in researches made by the group of study of concrete durability of UFG. The fact of metakaolin concretes shows great performance towards durability and mechanical strength is controversial, once the silica content is about 55%, which, theoretically, would result in a smaller volume of C-S-H, from the pozzolanic reaction. However, as it is a very fine material, its physical effect in concrete seems to be more prominent, besides, the alumina that there is in metakaolin also produces interesting hydrated compounds. This way, the goal of the present work is to evaluate the changes in the microstructure of concrete using three types of metakaolin, manufactured by the same company. The main differences between than is their fineness. The specific surface area, measured by BET method, varied from about 8 000 m²/kg to 31 000 m²/kg. Moreover, one of them – the coarser one – differs from the other because it has a high chemical and mineralogical purity. In order to have a better understanding of the properties of the three types of metakaolin, a wide characterization of the physical, chemical and mineralogical properties of this mineral admixtures were carried out. Concrete mixtures were than prepared for the purpose of knowing the influence of the characteristics of the metakaolins in the mechanical and durability related properties and microstructure of the concrete. Metakaolin concretes studied in this work showed significant improvement in mechanical strength, total porosity, pore refinement, electrical resistivity and non-steady state chloride migration. The evaluation of concrete microstructure shows that metakaolin promoted a densification of interfacial transition zone between the paste matrix and aggregate. Furthermore, there are indications suggesting that in metakaolin concrete can occur the formation of Friedel’s salt. Thus, it follows that the addition of the three different types of metakaolin had significantly changed the properties of concrete, with positive highlight for the properties associated to concrete durability, in which the benefits of the mineral admixtures were more pronounced.